2015
DOI: 10.1159/000437366
|View full text |Cite
|
Sign up to set email alerts
|

Twin-Twin Transfusion Syndrome in Cases with Suspected Close Proximity of Umbilical Cord Insertions

Abstract: We encountered 3 cases of twin-twin transfusion syndrome (TTTS), in which preoperative ultrasonography revealed that the cord insertion sites of the twins were close. Two cases were successfully treated with fetoscopic laser photocoagulation (FLP); however, the third case could not be treated surgically because fetoscopy revealed that the cord insertions formed a V-shaped joint above the placenta and that all chorionic vessels of the placental surface were shared by the twins. No residual anastomoses were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Repeat surgery for recurrent TTTS and reversal of TTTS were excluded; therefore, 156 surgeries in 156 patients were included in the final study. In one case, photocoagulation was ruled out on fetoscopy because placental cord insertions of both twins were very close and the whole placental area was shared by both fetuses …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeat surgery for recurrent TTTS and reversal of TTTS were excluded; therefore, 156 surgeries in 156 patients were included in the final study. In one case, photocoagulation was ruled out on fetoscopy because placental cord insertions of both twins were very close and the whole placental area was shared by both fetuses …”
Section: Resultsmentioning
confidence: 99%
“…In one case, photocoagulation was ruled out on fetoscopy because placental cord insertions of both twins were very close and the whole placental area was shared by both fetuses. 16 Preoperative patient characteristics are listed in Table 1. The most frequent indication for FLP was TTTS (85%, n = 132).…”
Section: Resultsmentioning
confidence: 99%
“…The same group later proposed a definition of proximate cord insertions based on 369 monochorionic placentas as lower than the fifth centile, which ranged from 3.3 to 4.0 cm across gestation [17]. Sato et al [8] reported successful SLPCV in 2 of 3 TTTS cases complicated by proximate cord insertions. Technical details of the SLPCV were not discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Fetoscopy in the third case demonstrated a V-shaped shared cord insertion site between the donor and recipient, and SLPCV was considered impossible because the vascular equator could not be properly identified [8]. Instead, the patient underwent amnioreduction followed by emergent cesarean delivery for fetal distress at 24 weeks' gestation [8]. In a case series by Gandhi et al [9], 1 of 6 TTTS cases with proximate cord insertions was treated with SLPCV, which resulted in dual fetal demise on postoperative day 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation